Disruptive Speech: A Discursive Analysis of Single Mother Memoirs and the Challenge to Compulsory Heterosexuality - Lind, Emily R. M. (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
This article examines the discursive construction of single motherhood in contemporary creative non-fiction. Specifically, I analyze the way single motherhood is imagined in Robin Silbergleid’s Texas Girl, Casey Goldberg, Beth Jones, and Pamela Ferdinand’s Three Wishes, and Andrea Askowitz’s My Miserable Lonely Lesbian Pregnancy. My analysis focuses particularly on the ways that these authors use the discourse of maternity to comment on their experience of compulsory heterosexuality.